Prehospital management of burns requiring specialized burn centre evaluation: a single physician-based emergency medical service experience - Ludovic Maudet; Mathieu Pasquier; Olivier Pantet; Roland Albrecht; Pierre-Nicolas Carron (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2020)
Abstract Background Emergency medical services regularly encounter severe burns. As standards of care are relatively well-established regarding their hospital management, prehospital care is comparatively poorly defined. The aim of this study was to describe burned patients taken care of by our physician-staffed emergency medical service (PEMS). Methods All patients directly transported by our PEMS to our burn centre between January 2008 and December 2017 were retrospectively enrolled. We specifically addressed three “burn-related” variables: prehospital and hospital burn size estimations, type and volume of infusion and pain assessment and management. We divided patients into two groups for comparison: TBSA < 20% and ≥ 20%. We a priori defined clinically acceptable limits of agreement in the small and large burn group to be ±5% and ± 10%, respectively. Results We included 86 patients whose median age was 26 years (IQR 12–51). The median prehospital TBSA was 10% (IQR 6–25). The difference between the prehospital and hospital TBSA estimations was outside the limits of agreement at 6.2%. The limits of agreement found in the small and large burn groups were − 5.3, 4.4 and − 10.1, 11, respectively. Crystalloid infusion was reported at a median volume of 0.8 ml/kg/TBSA (IQR 0.3–1.4) during the prehospital phase, which extrapolated over the first 8 h would equal to a median volume of 10.5 ml/kg/TBSA. The median verbal numeric rating scale on scene was 6 (IQR 3–8) and 3 (IQR 2–5) at the hospital (p < 0.001). Systemic analgesia was provided to 61 (71%) patients, predominantly with fentanyl (n = 59; 69%), followed by ketamine (n = 7; 8.1%). The median doses of fentanyl and ketamine were 1.7 mcg/kg (IQR 1–2.6) and 2.1 mg/kg (IQR 0.3–3.2), respectively. Conclusions We found good agreement in burn size estimations. The quantity of crystalloid infused was higher than the recommended amount, suggesting a potential risk for fluid overload. Most patients benefited from a correct systemic analgesia. These results emphasized the need for dedicated guidelines and decision support aids for the prehospital management of burned patients.